Efficacy of a povidone‐iodine foam dressing (Betafoam) on diabetic foot ulcer. Issue 1 (26th November 2019) - Gwak, Heui C.; Han, Seung H.; Lee, Jinwoo; Park, Sejin; Sung, Ki‐Sun; Kim, Hak‐Jun; Chun, Dongil; Lee, Kyungmin; Ahn, Jae‐Hoon; Kwak, Kyunghee; Chung, Hyung‐Jin
Abstract: This study aimed to assess the efficacy of a new povidone‐iodine (PVP‐I) foam dressing (Betafoam) vs foam dressing (Medifoam) for the management of diabetic foot ulcers. This study was conducted between March 2016 and September 2017 at 10 sites in Korea. A total of 71 patients (aged ≥19 years) with type 1/2 diabetes and early‐phase diabetic foot ulcers (Wagener classification grade 1/2) were randomised to treatment with PVP‐I foam dressing or foam dressing for 8 weeks. Wound healing, wound infection, patient satisfaction, and adverse events (AEs) were assessed. The PVP‐I foam and foam dressing groups were comparable in the proportion of patients with complete wound healing within 8 weeks (44.4% vs 42.3%, P = .9191), mean (±SD) number of days to complete healing (31.00 ± 15.07 vs 33.27 ± 12.60 days; P = .6541), and infection rates (11.1% vs 11.4%; P = 1.0000). Median satisfaction score (scored from 0 to 10) at the final visit was also comparable between groups (10 vs 9, P = .2889). There was no significant difference in AE incidence (27.8% vs 17.1%, P = .2836), and none of the reported AEs had a causal relationship with the dressings. The results of this study suggest that PVP‐I foam dressing has wound‐healing efficacy comparable with foam dressing, with no notable safety concerns. This study was funded by Mundipharma Korea Ltd and registered at ClinicalTrials.gov (identifier NCT02732886).